Development of an Analytical Software for Communication management in Project Management Offices - Firas Kh. Jaber, Assis. Prof Dr.; Faiq M. S. Al-Zwainy, Assis.Prof. Dr. (International Journal of Engineering and Technology, 2018)
This study deals with the problem of communication management system in Project Management Office (PMO) in Iraqi construction sectors. The main objective of this study was to estimate and develop the Communication Management System (CMS). Methodology: Visual basic language has been used to build analytical software which is (Communication Management Software). This software displays the overall information in every single project management office followed by the evaluation of the actuality of communication methods with two arithmetic equations so that estimate the effectiveness and barriers of Communication Management System. Statistical Package for the Social Sciences, SPSS vr.23.0 was used for Data analysis and determining the equations to calculate the efficiency and barriers of PMO; Developed Computer Software: Based on the data analysis results, it will provide computer software to calculate the efficiency and barriers of PMO and validation and verification of computer software followed by the discussion of the results. CMS was weighed depending on a questionnaire of ten project management engineers in Iraqi construction zones. Results showed that 100% stated to the simple usage of the software, and 75% of the research sample proven that the software discussed three matters which are cost, time, and performance. The result expressed that the half of the studied sample proved the CMS accuracy to valuation certainty of CMS. The 55% of the resulting sample expressed is very good software for both increasing the performance in the middle of the members of the Project Management Office. Evaluation of the proposed software indicated that it is effective in communication management in Project Management Office (PMO).Â Â